#84 Formulation of sustain release matrix tablet of anti-anginal drug based on Eudragid L 100-55: In-vitro drug release and kinetic approach - Rastogi, Yash; Bhatt, Shubham; Pathak, Anuj (Journal of Pharmaceutical Chemistry, 2022)
This study aims to design and evaluate oral sustained release matrix tablets of BCS class 2 anti-anginal drug using Eudragit L 100-55 as the retardant polymer and mannitol as a channeling agent for the delivery of anti-anginal drug as twice-daily dose. The tablets were made using the traditional wet granulation approach. Weight variation, hardness, friability, and drug content were all determined for the tablets. The pharmacopeial requirements were satisfied by all of the formulations. In-vitro dissolution studies were carried out in 900 mL of 0.1N HCl at 50 rpm for eight hours using a USP type II device (paddle technique). The zero-order, first-order, Higuchi, Hixson-Crowell, and Korsmeyer-Peppas equations have been used to investigate and describe the release profile from matrix tablets. In vitro dissolution studies found that the percent drug release dropped as polymer loading increased. The optimal composition was chosen based on solubility data comparisons with the innovator product F3 formulation (Eudragit L100-55 16% w/w of drug). The drug release profile of the optimized formulation was reasonably well controlled and homogeneous throughout the dissolving tests. As per the Korsmeyer–Peppas equation, the release of the drug of the improved formulation satisfies the Higuchi kinetic model (R2 = 0.99), and the process is non-Fickian/anomalous. To conclude, the current research reveals that oral sustained release anti-anginal tablets are indeed a better choice for generating a twice-daily medication. The product’s success in-vitro dissolution studies and release pattern suggests that it should be tested in-vivo.
Keywords: aaa